Race and the education of desire : Foucault's History of sexuality and the colonial order of things - Stoler, Ann Laura (Duke University Press, 1995)
Michel Foucault's History of Sexuality has been one of the most influential books of the last two decades. It has had an enormous impact on cultural studies and work across many disciplines on gender, sexuality, and the body. Bringing a new set of questions to this key work, Ann Laura Stoler examines volume one of History of Sexuality in an unexplored light. She asks why there has been such a muted engagement with this work among students of colonialism for whom issues of sexuality and power are so essential. Why is the colonial context absent from Foucault's history of a European sexual discourse that for him defined the bourgeois self? In Race and the Education of Desire, Stoler challenges Foucault's tunnel vision of the West and his marginalization of empire. She also argues that this first volume of History of Sexuality contains a suggestive if not studied treatment of race. Drawing on Foucault's little-known 1976 College de France lectures, Stoler addresses his treatment of the relationship between biopower, bourgeois sexuality, and what he identified as racisms of the state. In this critical and historically grounded analysis based on cultural theory and her own extensive research in Dutch and French colonial archives, Stoler suggests how Foucault's insights have in the past constrained -- and in the future may help shape -- the ways we trace the genealogies of race. Race and the Education of Desire will revise current notions of the connections between European and colonial historiography and between the European bourgeois order and the colonial treatment of sexuality. Arguing that a history of European nineteenth-century sexuality must also be a history of race, it will change the way we think about Foucault." from http://search.barnesandnoble.com (Jan. 25, 2011.).